HUBUNGAN PEMBELI DAN PEMASOK: KERJASAMA UNTUK MENINGKATKAN KEPUASAN DAN LOYALITAS PELANGGAN - Najib, Moh Farid (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
This article would like to explore the literatures has focused upon the relationship between buyer and supplier. The buyer and supplier relationship become a vehicle for assisting the strategic intention on the firm through inputs from key suppliers willing to help. Moreover, the concept of Customer Relationship Management (C.R.M) and Supplier Relationship Management (S.R.M) become new paradigm how enterprises focus on satisfying Customer. However, understanding buyer-setter relationship needs more open sharing information between them.